2002
DOI: 10.1139/w02-023
|View full text |Cite
|
Sign up to set email alerts
|

A N2-fixing endophyticBurkholderiasp. associated with maize plants cultivated in Mexico

Abstract: In the frame of a survey of potentially endophytic N2-fixing Burkholderia associated with maize in Mexico, its country of origin, the soil of an indigenous maize field near Oaxaca was studied. Under laboratory conditions, plant seedlings of two ancient maize varieties were used as a trap to select endophyte candidates from the soil sample. Among the N2 fixers isolated from inside plant tissues and able to grow on PCAT medium, the most abundant isolates belonged to genus Burkholderia (API 20NE, rrs sequences). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 48 publications
3
43
0
5
Order By: Relevance
“…nov., relative to other Burkholderia species. Strains Ppe8 T , were closely related, forming a cluster with strains BM16 and BM273 described in a previous study (Estrada et al, 2002), as well as with strain AB98 (Cruz et al, 2001). The similarity among the 16S rRNA gene sequences of these strains ranged from 99?2 to 99?9 %.…”
Section: Ardra and Phylogenetic 16s Rrna Gene Analysissupporting
confidence: 57%
See 1 more Smart Citation
“…nov., relative to other Burkholderia species. Strains Ppe8 T , were closely related, forming a cluster with strains BM16 and BM273 described in a previous study (Estrada et al, 2002), as well as with strain AB98 (Cruz et al, 2001). The similarity among the 16S rRNA gene sequences of these strains ranged from 99?2 to 99?9 %.…”
Section: Ardra and Phylogenetic 16s Rrna Gene Analysissupporting
confidence: 57%
“…Two isolates from pineapple showed an amplified 16S rDNA restriction analysis (ARDRA) pattern identical to the sugarcane isolate Ppe8 T (Cruz et al, 2001). Recently, the analysis of N 2 -fixing bacteria associated with maize and coffee plants grown under field conditions revealed the presence of B. vietnamiensis, as well as the richness of novel diazotrophic bacterial species belonging to the genus Burkholderia (Estrada-de los Santos et al, 2001;Estrada et al, 2002). These N 2 -fixing isolates exhibited high diversity in the ARDRA profiles.…”
Section: Introductionmentioning
confidence: 99%
“…associated with maize plants cultivated in Mexico by Estrada et al (2002) showed that all the Burkholderia isolates could reduce acetylene…”
Section: Resultsmentioning
confidence: 99%
“…De otra parte se ha manifestado que las bacterias endófitas son considerados microorganismos con actividad inhibitoria contra diversos patógenos y la eficiencia de esta actividad según lo han demostrado diversos estudios, es debido a que los microorganismos endófitos pueden establecer una relación mutualista con la planta desde su interior, mediante el cual les confieren protección contra factores bióticos y abióticos adversos (SCHULZ y BOYLE 2006), promueven el crecimiento en las plantas (TSAVKELOVA et al, 2007), aumentan la resistencia a enfermedades (CHANWAY, 1998), contribuyen a la fijación biológica de nitrógeno (JIMENEZ et al, 1997;ESTRADA et al, 2002), bioremediación (NEWMAN Y REYNOLDS, 2005) y producción de sideróforos o inmunidad (SESSITSCH et al, 2002).…”
Section: Discussionunclassified